Shear-assisted laser transfer of metal nanoparticle ink to an elastomer substrate - Shin, Wooseop; Lim, Jaemook; Lee, Younggeun; Park, Sewoong; Kim, Hyeonseok; Cho, Hyunmin; Shin, Jaeho; Yoon, Yeosang; Lee, Habeom; Kim, Hyun Jong; Han, Seungyong; Ko, Seung Hwan; et al. (Materials, 2018)
Selective laser sintering of metal nanoparticle ink is an attractive technology for the creation of metal layers at the microscale without any vacuum deposition process, yet its application to elastomer substrates has remained a highly challenging task. To address this issue, we introduced the shear-assisted laser transfer of metal nanoparticle ink by utilizing the difference in thermal expansion coefficients between the elastomer and the target metal electrode. The laser was focused and scanned across the absorbing metal nanoparticle ink layer that was in conformal contact with the elastomer with a high thermal expansion coefficient. The resultant shear stress at the interface assists the selective transfer of the sintered metal nanoparticle layer. We expect that the proposed method can be a competent fabrication route for a transparent conductor on elastomer substrates.
Keywords: Conformal contacts; Fabrication routes; Laser transfer; Selective laser sintering; Stretchable electronics; Thermal expansion coefficients; Transparent conductors; Vacuum deposition process; Laser transfer; Metal nanoparticle ink; Stretchable electronics